Long‐acting injectable antipsychotics in early psychosis: a literature review. Issue 3 (24th January 2013) - Emsley, Robin; Chiliza, Bonginkosi; Asmal, Laila; Mashile, Mpogisheng; Fusar‐Poli, Paolo
Abstract Aim There are sound reasons for considering the use of long‐acting injectable antipsychotics early in the course of schizophrenia. We reviewed available literature on the subject. Method We conducted an electronic database search and critically reviewed all studies in which a long‐acting injectable antipsychotic was evaluated in early psychosis patients. Results There is a need for well‐designed studies as most of those reported were open‐label and non‐comparative, and samples were frequently small. Conclusions The available evidence does suggest that long‐acting injectable antipsychotics can be used safely and effectively in early stages of the illness, and that they may be associated with better outcomes than with oral medications. However, this is largely supported by evidence from naturalistic cohort studies and a small number of controlled trials of risperidone long‐acting injection. Evidence for olanzapine and paliperidone long‐acting injectables in particular is limited.